(untitled) (Revista de Psicología, 2025)
This paper aims to clarify the false attribution of masochism to the feminine and to contribute tools for the clinical detection of the phenomenon of male masochism to current psychoanalytic practice. The guiding question is how the formulas of sexuation in Jacques Lacan’s seminar “Even” allow us to demonstrate the attribution of the masochistic fantasy to the masculine side. Lacan conceives castration from a logical perspective, no longer from mythology (Oedipus complex), which allows him to abandon the definition of femininity based on sexual anatomy and proposes formulas of sexuation. With this contribution, he achieves two advances. First, it brings psychoanalysis closer to the field of science (mathematics, logic, topology, linguistics). Thus, Lacan moves from myth to matheme and rescues Freud from obscurantist complaints related to totem and taboo. Second, he questions the idea that femininity is regulated by the norm of the phallus, therefore, female sexuality is not resolved by having. The contribution of this work is to draw the consequences of these advances. First, by situating the two modes of enjoyment on the feminine side and the single mode of enjoyment on the masculine side. Then, by reviewing the concepts of fantasy and masochism in light of the concept of perversion, following Freud’s text “They Beat a Child.” The conclusion is that perversion is a neurotic fantasy and the masochistic fantasy is masculine.